Failure of primary ACL repair with dynamic intraligamentary stabilization may result in a high risk of two‐stage ACL reconstruction: a case series of ten patients - Riccardo Cristiani; Caroline Mouton; Renaud Siboni; Charles Pioger; Romain Seil (Journal of Experimental Orthopaedics)
Abstract Purpose Dynamic Intraligamentary Stabilization (DIS) is a technique for the repair of acute anterior cruciate ligament (ACL) injuries. The purpose of this study was to investigate the potential challenges of ACL reconstruction (ACLR) following failure of DIS. Methods A retrospective analysis of patients with failure of primary ACL repair performed with DIS was undertaken. Failure was defined as abnormal knee laxity (positive Lachman and/or pivot shift) and/or severely restricted range of motion. Medical and surgical records were reviewed and preoperative standard anteroposterior and lateral X‐rays were assessed. Results Between July 2015 and May 2022, 10 patients (3 males, 7 females, median age 28 years, range 18–52 years) with failure of DIS were referred to and surgically treated at a single centre. In four patients, single‐stage ACLR was performed following the removal of the tibial monoblock. In six patients, arthrofibrosis and excessive tibial tunnel enlargement following the removal of the monoblock prevented single‐stage ACLR. These patients underwent arthroscopic arthrolysis and tibial tunnel bone grafting as a first‐stage revision procedure. Conclusion In the present case series, single‐stage ACLR was performed in only four (40%) of ten patients following failure of ACL repair with DIS. Arthrofibrosis and excessive tibial tunnel enlargement following the removal of the monoblock prevented single‐stage ACLR in six (60%) patients. It is important for clinicians to inform patients that, in the event of failure of ACL repair with DIS, they may run a high risk of undergoing two‐stage ACLR. Level of Evidence Level IV, Case Series.